The Precursor Hypothesis of Sponge Kleptocnidism: Development of Nematocysts in Haliclona cnidata sp. nov. (Porifera, Demospongiae, Haplosclerida) - Schellenberg, Johannes; Reichert, Jessica; Hardt, Martin; Schmidtberg, Henrike; Kämpfer, Peter; Glaeser, Stefanie P.; Schubert, Patrick; Wilke, Thomas (Frontiers in Marine Science, 2019)
Marine sponges thrive in benthic environments despite intense spatial competition and predator pressure. The sessile filter-feeders usually compensate their lack of physical defense and behavioral escape by a high level of bioactivity. In the stinging black sponge (Haliclona cnidata sp. nov.), these chemical defense mechanisms are complemented by “cellular weapons”—functional nematocysts likely acquired from cnidarians (kleptocnidism). Whereas, kleptocnidism might be facilitated by a close contact with cnidarian donors, preliminary investigations suggest that the stinging black sponge sustains nematocysts even if kept apart from cnidarians. As the underlying mechanisms causing this phenomenon remain unknown, the development of its nematocysts was studied in both presence and absence of potential cnidarian donors. First, we compared inherent nematocysts of adult sponge individuals with foreign nematocysts of co-cultivated cnidarians to identify potential donors. Second, we experimentally assessed the donor-independent and donor-dependent development of inherent and foreign nematocysts within cultures of sponge cell aggregates (SCAs). The inherent nematocysts comprised two specific types that both differed from those of the eight co-cultivated cnidarians. Specifically, we showed that the number of sponge-inherent nematocysts increased in SCAs over time in the absence of potential donors. Numbers of supplied foreign nematocysts, however, did not increase in the SCAs. We conclude that the observed increase of inherent nematocysts is due to the maturation of nematocyst precursor cells. Given these findings, we here propose the precursor hypothesis of sponge kleptocnidism. Accordingly, nematocyst precursors or immature nematocyte-nematocyst complexes might be initially acquired by sponges through filtration, maintained in sponge tissues, and nurtured to fully functioning nematocyte-nematocyst complexes. The underlying evolutionary processes are likely facilitated by bacteria-derived secondary metabolites and photosynthetically active dinoflagellates. Due to a simple body plan and the in vitro proliferation capacity of sponge cells, H. cnidata sp. nov. may serve as a novel evolutionary model system to further assess fundamental research questions regarding kleptocnidism. This study not only sheds new light on kleptocnidism in sponges, it also calls for a holobiontic view at defense mechanisms that involves the actual sponge, cnidarian nematocysts, dinoflagellate endosymbionts, and a complex microbial community. Life Science Identifier (LSID): urn:lsid:zoobank.org:act:509A075A-5D5D-417F-811E-52D3421D48BC